Kajian pemanfaatan ruang kawasan pesisir studi kasus kawasan permukiman kumuh Kelurahan Padarni Kabupaten Manokwari - Adityo Dwi Nugroho (Program Pascasarjana Universitas Papua, 2019)
Manokwari is a coastal city and the capital city of the Province which is considered as very strategic and growing city, making Manokwari more attract for jobs seeker. Many low- income people who migrate to Manokwari make densely populated and slum squatter settlements inevitable. Padarni Coastal Area is one of the urban areas with very poor environmental conditions, Irregular, disaster-prone settlements as well as basic facilities and infrastructure have not been realized properly so that the community cannot move and live properly. The results of the study were 6 causes of slum conditions: Socio-cultural Characteristics, level of urbanization, limited land, accessibility, facilities and infrastructure, and weak of government policies. With the concept of waterfront development, settlement arrangement activities are directed at the utilization of local potential, phasing improvement in the quality of settlements and sustainable slums prevention.